Education Through Movement in Research Practice - Barbara Anna Bilewicz-Kuźnia; Manuela Valentini; Angelica Nocciolino (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Several multidisciplinary and international studies have shown that learning processes can be constructed by means of embodiment, through education in or of the body and contribute to the person-child's cognitive, social, emotional and relational development, considered in its uniqueness, as well as to their health. The educator and doctor Jean Le Boulch is thought to be the greatest exponent in the science of movement, with his Psychomotor learning theory. No intellectual progress can be accomplished without the help of the body, and motor skills require the use of psychological factors, therefore, to a Human Being, given that it is made up of a set of many units, it must therefore be used globally. Through studies included in this research it was further stressed that psychomotor offers important advantages for the integral development of a child. The article is a review of scientific research on educational psychomotor and its numerous benefits for the child's integral development. It emphasized that harmony between the mind and the body promotes positive growth processes of the individual.